Fostering Unity: Christological and Eschatological Foundations in Pauline Ethics - Kwon, Youngju (The expository times, 2025)
This study argues that Paul’s exhortations in Romans 14:1–12 are deeply rooted in his Christological and eschatological convictions. By analyzing the tension between the strong and the weak, this study proposes that Paul’s call for mutual welcoming is not a mere social recommendation but a profound theological imperative. Through careful textual analysis, this study highlights how Paul integrates Christological and eschatological motifs to shape his ethical instructions. The identification of Jesus Christ as both the Lord and the eschatological judge reinforces the theological basis for Paul’s exhortations to prioritize love and mutual welcoming over judgment and contempt. Paul’s vision of a unified community reflects his eschatological hope of Gentiles and Jews being united as the new people of God. In conclusion, the study affirms that Paul’s exhortations are not ad hoc responses to pastoral challenges but are firmly grounded in his coherent theological convictions. By interweaving Christological and eschatological motifs, Paul presents a compelling vision of the Kingdom of God, where Christ’s lordship and the eschatological awareness urge believers to transcend their differences and live in a manner that reflects peace and unity.